Antibacterial polycarboxylate water reducing agent and preparation method thereof

CN122685344BActive Publication Date: 2026-10-23SICHUAN YU CONCRETE BUILDING MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611184788.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-06
Publication Date
2026-10-23
Estimated Expiration
2046-08-06

AI Technical Summary

Technical Problem

[0004]本发明的目的在于:提供了一种抗菌性聚羧酸减水剂及其制备方法,解决了目前在混凝土配置过程中通过直投式添加抗菌组分来抑制SRB的生长和繁殖,很难保证抗菌组分在胶凝材料体系中的均匀分布,导致混凝土整体抗菌效果不佳的问题

Benefits of technology

[0022]1.本发明一种抗菌性聚羧酸减水剂,利用减水剂在混凝土搅拌过程中随水均匀分散的特性,将其作为了硫酸盐还原菌抑菌物的负载载体;本发明将硫酸盐还原菌抑菌物(氨基环糊精包埋1,8-二氯蒽醌)预先负载于介孔二氧化硅中,再与含有二硫键的聚羧酸聚合物连接,再混合于聚羧酸减水剂母液中,形成完整的含SRB抑菌物的减水剂体系;该体系中SRB抑菌物随聚羧酸减水剂组分均匀分散至混凝土中,克服了直接添加抗菌组分分散不均的缺陷;在混凝土强碱性环境的作用下,会触发抑菌物从介孔二氧化硅中部分释放,但是pH触发的抑菌物释放率有限,只能够起到初步抑菌;当混凝土处于SRB易定植环境,微生物从混凝土表面开始向内部侵蚀时,二硫键能够在SRB代谢产生的H2S作用下被还原,进一步促进抑菌物释放,达到抑制SRB继续生长、繁殖的目的,抑制微生物向混凝土内部的扩蚀;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122685344B_ABST
    Figure CN122685344B_ABST
Patent Text Reader

Abstract

The application discloses an antibacterial polycarboxylic acid water reducing agent and a preparation method thereof, and belongs to the technical field of concrete admixtures. The antibacterial polycarboxylic acid water reducing agent comprises a polycarboxylic acid water reducing agent mother liquor and a bacteriostatic composition. The polycarboxylic acid water reducing agent mother liquor comprises a slow-release polycarboxylic acid polymer containing a phosphate ester and silane coupling agent modified mesoporous silicon dioxide, the silane coupling agent modified mesoporous silicon dioxide is loaded with a broad-spectrum bacteriostatic agent, and the bacteriostatic composition comprises a polycarboxylic acid polymer containing a disulfide bond and surface epoxy modified disulfide bond modified mesoporous silicon dioxide, and the surface epoxy modified disulfide bond modified mesoporous silicon dioxide is loaded with a sulfate-reducing bacteria bacteriostatic agent. The antibacterial component is directly added to inhibit the growth and reproduction of SRB in the concrete configuration process, and it is difficult to guarantee the uniform distribution of the antibacterial component in the cementitious material system, thereby solving the problem of poor overall antibacterial effect of concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of concrete admixture technology, and relates to an antibacterial polycarboxylate superplasticizer and its preparation method. Background Technology

[0002] Microbial corrosion can severely affect almost all existing materials, damaging their structure and properties, and causing significant safety hazards and property losses in buildings, transportation pipelines, industrial environments (petrochemicals, etc.), and marine environments. Microbial corrosion is an obstacle to the long-term use of marine concrete, and solving it can help achieve sustainable coastal city construction. The microorganisms involved in concrete microbial corrosion mainly include sulfate-reducing bacteria (SRB). SRB are widely distributed in water bodies, soil, and other environments, and therefore inevitably come into contact with reinforced concrete facilities. SRB dominate corrosion in anaerobic environments. SRB are a group of prokaryotic microorganisms that are physiologically and morphologically different and obtain energy by oxidizing organic compounds or molecular hydrogen, reducing sulfates, sulfites, thiosulfates, and even elemental sulfur (as the final electron acceptor in its electron transport chain) to H2S. SRB and sulfur-oxidizing bacteria (SOB) work synergistically to cause severe concrete corrosion. SOB can oxidize the H2S generated by SRB metabolism to produce H2SO4, causing corrosion to begin from the concrete surface and penetrate inward.

[0003] Therefore, antibacterial components are currently added directly during the concrete mixing process to inhibit the growth and reproduction of SRB. However, this direct addition of antibacterial components makes it difficult to ensure the uniform distribution of antibacterial components in the cementitious material system, which will lead to poor overall antibacterial effect of the concrete. Summary of the Invention

[0004] The purpose of this invention is to provide an antibacterial polycarboxylate superplasticizer and its preparation method, which solves the problem that in the current concrete mixing process, it is difficult to ensure the uniform distribution of antibacterial components in the cementitious material system when adding antibacterial components directly to inhibit the growth and reproduction of SRB, resulting in poor overall antibacterial effect of concrete.

[0005] The technical solution adopted in this invention is as follows:

[0006] An antibacterial polycarboxylate superplasticizer includes a polycarboxylate superplasticizer mother liquor and an antibacterial composition;

[0007] The polycarboxylate superplasticizer mother liquor includes a slow-release polycarboxylate polymer containing phosphate esters and silane coupling agent modified mesoporous silica, wherein a broad-spectrum antibacterial agent is loaded on the silane coupling agent modified mesoporous silica.

[0008] The antibacterial composition comprises a polycarboxylic acid polymer containing disulfide bonds and surface-epoxy-modified disulfide-bonded mesoporous silica, on which sulfate-reducing antibacterial agents are loaded.

[0009] Furthermore, the polycarboxylic acid polymer containing disulfide bonds is obtained by copolymerizing isopentenyl polyoxyethylene ether macromonomer, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid and a polymerizable intermediate containing disulfide bonds under the action of an initiator and a chain transfer agent.

[0010] Furthermore, the phosphate-containing slow-release polycarboxylic acid polymer is obtained by copolymerizing vinylphosphonic acid, acrylic acid, and functionalized polyether macromonomers under the action of an initiator and a chain transfer agent; wherein, the functionalized polyether macromonomer is a polyether macromonomer obtained by pre-reacting HPEG-2400 with succinic anhydride and then esterifying it with phosphate-containing polyethylene glycol.

[0011] Furthermore, surface-epoxy-modified disulfide-bonded mesoporous silica was prepared by the following method: Triblock surfactant P123 was dissolved in deionized water at 35-40℃, and tetraethyl orthosilicate, bis-[3-(triethoxysilyl)propyl]-disulfide, aluminum isopropoxide, and hydrochloric acid were added and stirred for 24-28 hours. After the reaction, the reaction solution was transferred to a hydrothermal reactor with a polytetrafluoroethylene liner and crystallized at 90-110℃ for 55-56 hours. After crystallization, the solution was filtered, washed with deionized water until neutral, and then... The raw mesoporous silica powder was obtained by drying at 0–80℃ for 22–24 hours. The raw mesoporous silica powder was transferred to a Soxhlet extractor, acidified ethanol was added, and the mixture was refluxed at 80–90℃ for 40–48 hours. The mixture was filtered, washed with deionized water until neutral, and dried under vacuum at 60–80℃ to obtain disulfide-modified mesoporous silica. The molar ratio of triblock surfactant P123, tetraethyl orthosilicate, bis-[3-(triethoxysilyl)propyl]-disulfide, aluminum isopropoxide, and hydrochloric acid was 0.017:1:0.2:0.04:6.

[0012] Disulfide-modified mesoporous silica was dispersed in anhydrous ethanol, and 3-glycidyl etheroxypropyltrimethoxysilane was added. The mixture was refluxed at 60–80 °C for 4–8 hours, filtered, washed with anhydrous ethanol, and vacuum dried to obtain epoxy-modified disulfide-modified mesoporous silica. The mass ratio of disulfide-modified mesoporous silica to 3-glycidyl etheroxypropyltrimethoxysilane was 2:1.

[0013] Furthermore, the broad-spectrum antibacterial agent is 8-hydroxyquinoline zinc salt; the sulfate-reducing antibacterial agent is 1,8-dichloroanthraquinone encapsulated in aminocyclodextrin.

[0014] Further, the aminocyclodextrin-encapsulated 1,8-dichloroanthraquinone was prepared by the following method: mono-6-amino-β-cyclodextrin was dissolved in deionized water to prepare a 5% (w / w) aminocyclodextrin aqueous solution; 1,8-dichloroanthraquinone was dissolved in dimethyl sulfoxide to prepare a 20 mg / mL anthraquinone organic solution; under light-protected stirring at 20-30°C, the anthraquinone organic solution was added dropwise to the aminocyclodextrin aqueous solution, with a molar ratio of mono-6-amino-β-cyclodextrin to 1,8-dichloroanthraquinone of 1:0.6; after the addition was complete, stirring was continued for 6 hours in the dark, followed by vacuum distillation. The remaining liquid was pre-frozen at -40 to -20°C for 3 hours, then freeze-dried for 30 hours, and stored in a sealed container in the dark to obtain aminocyclodextrin-encapsulated 1,8-dichloroanthraquinone.

[0015] Furthermore, the surface-epoxy-modified disulfide-bonded mesoporous silica was loaded with sulfate-reducing antibacterial agents using the following method: 1,8-dichloroanthraquinone, encapsulated with aminocyclodextrin, was dissolved in N,N-dimethylformamide to prepare a 10% (w / w) loading solution; the surface-epoxy-modified disulfide-bonded mesoporous silica was dispersed in the above loading solution, with a mass ratio of surface-epoxy-modified disulfide-bonded mesoporous silica to aminocyclodextrin-encapsulated 1,8-dichloroanthraquinone of 1:0.3; impregnation loading was carried out by stirring at room temperature for 24 hours, with the pH controlled at 7.0-8.0 during the impregnation loading process; after impregnation loading, the silica was filtered, washed 2-3 times with anhydrous ethanol, and vacuum dried at 40-50°C to constant weight. The silica was then stored in a sealed container away from light to obtain surface-epoxy-modified disulfide-bonded mesoporous silica loaded with sulfate-reducing antibacterial agents.

[0016] Furthermore, silane coupling agent-modified mesoporous silica loaded with a broad-spectrum antibacterial agent was prepared by the following method: SBA-15 mesoporous silica was dispersed in anhydrous ethanol, and silane coupling agent KH-550 was added, with a mass ratio of KH-550 to SBA-15 mesoporous silica of 0.15:1. The mixture was refluxed at 60–80 °C for 6 hours, filtered, washed with anhydrous ethanol, and vacuum dried to obtain silane coupling agent-modified mesoporous silica; 8-hydroxyquinoline zinc salt was dispersed in a 15% (v / v) ethanol-water mixed solution and sonicated for 20–40 minutes. A dispersion of 2% (w / w) zinc 8-hydroxyquinoline salt was prepared, which was used as a loading solution. Silane coupling agent-modified mesoporous silica was dispersed in the loading solution at a mass ratio of 1:0.2 to zinc 8-hydroxyquinoline salt. The mixture was stirred at room temperature for 24 hours for impregnation loading. After impregnation loading, the mixture was filtered, washed, and vacuum dried to obtain silane coupling agent-modified mesoporous silica loaded with a broad-spectrum antibacterial agent.

[0017] A method for preparing an antibacterial polycarboxylate superplasticizer includes the following steps:

[0018] S1. Preparation of polycarboxylate superplasticizer mother liquor: Silane coupling agent modified mesoporous silica loaded with broad-spectrum antibacterial agent is added to a slow-release polycarboxylate polymer containing phosphate ester, and ultrasonically dispersed for 20-40 min to obtain polycarboxylate superplasticizer mother liquor; the mass ratio of silane coupling agent modified mesoporous silica loaded with broad-spectrum antibacterial agent to slow-release polycarboxylate polymer containing phosphate ester is 1:16.

[0019] S2. Preparation of antibacterial composition: A polycarboxylic acid polymer containing disulfide bonds is dissolved in deionized water to prepare a 15% (w / w) solution. Surface-epoxy-modified disulfide bond-modified mesoporous silica loaded with sulfate-reducing bacteria inhibitors is added. The mass ratio of the polycarboxylic acid polymer containing disulfide bonds to the surface-epoxy-modified disulfide bond-modified mesoporous silica loaded with sulfate-reducing bacteria inhibitors is 20:1. The mixture is stirred and reacted for 12 hours at pH 8.0–9.0 and temperature 35–45°C to obtain the antibacterial composition.

[0020] S3. Compounding: The polycarboxylate superplasticizer mother liquor and the antibacterial composition are compounded at a mass ratio of 14:(3.0~3.6) and stirred evenly to obtain the antibacterial polycarboxylate superplasticizer.

[0021] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0022] 1. This invention discloses an antibacterial polycarboxylate superplasticizer, utilizing the property of the superplasticizer to disperse uniformly with water during concrete mixing, thus serving as a loading carrier for sulfate-reducing bacteria (SRB) inhibitors. In this invention, the SRB inhibitor (aminocyclodextrin-embedded 1,8-dichloroanthraquinone) is pre-loaded into mesoporous silica, then linked with a disulfide-bonded polycarboxylate polymer, and finally mixed into the polycarboxylate superplasticizer mother liquor to form a complete superplasticizer system containing SRB inhibitors. In this system, the SRB inhibitors are uniformly dispersed into the concrete along with the polycarboxylate superplasticizer components. In this process, the defects of uneven dispersion of directly added antibacterial components are overcome; under the action of the strongly alkaline environment of concrete, the antibacterial agent will be partially released from the mesoporous silica, but the release rate of the antibacterial agent triggered by pH is limited and can only play a preliminary role in inhibiting bacteria; when the concrete is in an environment where SRB can easily colonize, and microorganisms begin to erode from the concrete surface to the interior, the disulfide bonds can be reduced under the action of H2S produced by SRB metabolism, further promoting the release of antibacterial agents, thereby inhibiting the continued growth and reproduction of SRB and inhibiting the spread of microorganisms into the interior of the concrete;

[0023] 2. This invention modifies mesoporous silica by introducing a silane coupling agent loaded with 8-hydroxyquinoline zinc salt into the mother liquor of polycarboxylate superplasticizer, thereby utilizing the broad-spectrum antibacterial activity of 8-hydroxyquinoline zinc salt to inhibit the growth of bacteria, molds and other microorganisms during the storage of the superplasticizer. Attached Figure Description

[0024] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly described below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort, wherein:

[0025] Figure 1 This is a method for preparing an antibacterial polycarboxylate superplasticizer;

[0026] Figure 2 These are comparative images of the surface corrosion effects of the specimens in Experimental Example 2 of this invention; wherein, Figure 2 (a) is a SEM image of the corroded surface of the specimen in test group D1; Figure 2 (b) is a SEM image of the corroded surface of the sample in test group S1. Detailed Implementation

[0027] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only for explaining the invention and are not intended to limit the invention; that is, the described embodiments are merely some embodiments of the invention, not all embodiments. The components of the embodiments of the invention described and shown in the accompanying drawings can generally be arranged and designed in various different configurations.

[0028] Therefore, the following detailed description of the embodiments of the invention provided in the accompanying drawings is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the invention without inventive effort are within the scope of protection of the invention.

[0029] It should be noted that relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.

[0030] The features and performance of the present invention will be further described in detail below with reference to embodiments.

[0031] This invention provides an antibacterial polycarboxylate superplasticizer, comprising a polycarboxylate superplasticizer mother liquor and an antibacterial composition;

[0032] The polycarboxylate superplasticizer mother liquor includes a slow-release polycarboxylate polymer containing phosphate esters and silane coupling agent modified mesoporous silica, wherein a broad-spectrum antibacterial agent is loaded on the silane coupling agent modified mesoporous silica.

[0033] The antibacterial composition comprises a polycarboxylic acid polymer containing disulfide bonds and surface-epoxy-modified disulfide-bonded mesoporous silica, on which sulfate-reducing antibacterial agents are loaded.

[0034] In the following examples, the polycarboxylic acid polymer containing disulfide bonds is obtained by copolymerization of isopentenyl polyoxyethylene ether macromonomer, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, and a polymerizable intermediate containing disulfide bonds under the action of an initiator and a chain transfer agent; wherein, the polymerizable intermediate containing disulfide bonds is prepared by the following method: using glycidyl methacrylate and cystamine in a molar ratio of 1:1 as reactants, under the catalysis of triethylamine, the reaction is carried out at 25-30 °C for 5 hours in an inert gas atmosphere to obtain the polymerizable intermediate containing disulfide bonds; the amount of triethylamine added is 0.2% of the total mass of glycidyl methacrylate and cystamine;

[0035] A polycarboxylic acid polymer containing disulfide bonds was prepared by the following method: 40g of isopentenyl polyoxyethylene ether macromonomer (Mn≈2400), 5g of acrylic acid, 0.8g of 2-acrylamido-2-methylpropanesulfonic acid, and 0.5g of the polymerizable intermediate containing disulfide bonds prepared by the above method were dissolved in 60g of deionized water. Oxygen was removed by purging with nitrogen, and the temperature was raised to 65℃. A free radical copolymerization reaction was carried out for 5 hours in the presence of 0.12g of ammonium persulfate and 0.08g of mercaptoethanol to obtain the polycarboxylic acid polymer containing disulfide bonds. Specifically, when using ammonium persulfate, 0.12g of ammonium persulfate was first dissolved in 5g of water and stirred evenly before use; similarly, 0.08g of mercaptoethanol was first dissolved in 5g of water and stirred evenly before use.

[0036] In the following examples, the phosphate-containing slow-release polycarboxylic acid polymer is obtained by copolymerizing vinylphosphonic acid, acrylic acid, and functionalized polyether macromonomers under the action of an initiator and a chain transfer agent; wherein, the functionalized polyether macromonomer is a polyether macromonomer obtained by pre-reacting HPEG-2400 with succinic anhydride and then esterifying it with phosphate-containing polyethylene glycol.

[0037] The sustained-release polycarboxylate polymer containing phosphate esters was prepared by the following independently developed method disclosed by the applicant: 100g HPEG-2400 (methyl allyl alcohol polyoxyethylene ether, Mn=2400) was first reacted with succinic anhydride to introduce -COOH, and then esterified with phosphate-containing polyethylene glycol to obtain a functionalized polyether macromonomer (containing -COO-CH2-COO- linker groups). The functionalized polyether macromonomer, 25g acrylic acid, 3.5g vinylphosphonic acid, and 0.8g mercaptoacetic acid were then dissolved in 150g deionized water. N2 was passed through the solution for 30 minutes, and the temperature was raised to 60℃. An ammonium persulfate solution was added dropwise (dropping time was 2 hours). The ammonium persulfate solution was obtained by dissolving 1.2g of ammonium persulfate in 20g of deionized water. After the addition was completed, the temperature was maintained for 2 hours. Finally, the solution was cooled, and the pH was adjusted to 6.5 with NaOH to obtain a pale yellow liquid with a solid content of 40%. The pale yellow liquid is a slow-release polycarboxylic acid polymer containing phosphate esters. This product is a phosphate ester-type polycarboxylic acid water-reducing agent with slow-release function that the applicant has independently developed.

[0038] In the following examples, surface-epoxy-modified disulfide-bonded mesoporous silica was prepared by the following method: 11.6 g of triblock surfactant P123 was dissolved in 360 mL of deionized water at 35-40 °C. After stirring until homogeneous, the mixture was prepared by adding tetraethyl orthosilicate, bis-[3-(triethoxysilyl)propyl]-disulfide, aluminum isopropoxide, and hydrochloric acid in a molar ratio of 0.017:1:0.2:0.04:6. The mixture was then stirred further. The reaction mixture was stirred for 24 hours. After the reaction was completed, the reaction solution was transferred to a hydrothermal reactor with a polytetrafluoroethylene liner and crystallized at 100°C for 55 hours. After crystallization, the mixture was filtered, washed with deionized water until neutral, and dried at 70°C for 24 hours to obtain mesoporous silica powder. The mesoporous silica powder was transferred to a Soxhlet extractor, acidified ethanol was added, and the mixture was refluxed at 85°C for 48 hours. After filtration, the mixture was washed with deionized water until neutral and dried under vacuum at 70°C to obtain disulfide bond modified mesoporous silica.

[0039] 5 g of disulfide-modified mesoporous silica was dispersed in 100 mL of anhydrous ethanol, and 2.5 g of 3-glycidyl etheroxypropyltrimethoxysilane was added. The mixture was refluxed at 70 °C for 6 hours. After filtration, washing with anhydrous ethanol, and vacuum drying, surface-epoxy-modified disulfide-modified mesoporous silica was obtained. The specific surface area of ​​the surface-epoxy-modified disulfide-modified mesoporous silica was 511 ± 15 m². 2 / g, pore volume is 0.85±0.03 cm³ 3 / g, with an average pore size of 6.8±0.3nm.

[0040] In the following examples, the broad-spectrum antibacterial agent is 8-hydroxyquinoline zinc salt; the sulfate-reducing antibacterial agent is 1,8-dichloroanthraquinone encapsulated in aminocyclodextrin.

[0041] In the following examples, the aminocyclodextrin-encapsulated 1,8-dichloroanthraquinone was prepared by the following method: mono-6-amino-β-cyclodextrin was dissolved in deionized water to prepare a 5% (w / w) aminocyclodextrin aqueous solution; 1,8-dichloroanthraquinone was dissolved in dimethyl sulfoxide to prepare a 20 mg / mL anthraquinone organic solution; under light-protected stirring at 25°C, the anthraquinone organic solution was added dropwise to the aminocyclodextrin aqueous solution, with a molar ratio of mono-6-amino-β-cyclodextrin to 1,8-dichloroanthraquinone of 1:0.6; after the addition was complete, stirring was continued for 6 hours in the dark, followed by vacuum distillation. The remaining liquid was pre-frozen at -30°C for 3 hours, then freeze-dried for 30 hours, and stored in a sealed container in the dark to obtain aminocyclodextrin-encapsulated 1,8-dichloroanthraquinone.

[0042] In the following examples, surface-epoxy-modified disulfide-bonded mesoporous silica was loaded with sulfate-reducing antibacterial agents using the following method: 1,8-dichloroanthraquinone encapsulated with aminocyclodextrin was dissolved in N,N-dimethylformamide to prepare a 10% (w / w) loading solution; surface-epoxy-modified disulfide-bonded mesoporous silica was dispersed in the above loading solution, with a mass ratio of surface-epoxy-modified disulfide-bonded mesoporous silica to aminocyclodextrin-encapsulated 1,8-dichloroanthraquinone of 1:0.3; impregnation loading was carried out by stirring at room temperature for 24 hours, with the pH controlled at 7.0~8.0 during the impregnation loading process; after impregnation loading, the silica was filtered, washed three times with anhydrous ethanol, and vacuum dried at 45°C to constant weight. The silica was then stored in a sealed container away from light to obtain surface-epoxy-modified disulfide-bonded mesoporous silica loaded with sulfate-reducing antibacterial agents.

[0043] In the following examples, silane coupling agent-modified mesoporous silica loaded with a broad-spectrum antibacterial agent was prepared by the following method: SBA-15 mesoporous silica was dispersed in anhydrous ethanol, and silane coupling agent KH-550 was added, with a mass ratio of KH-550 to SBA-15 mesoporous silica of 0.15:1. The mixture was refluxed at 70°C for 6 hours, filtered, washed with anhydrous ethanol, and vacuum dried to obtain silane coupling agent-modified mesoporous silica; 8-hydroxyquinoline zinc salt was dispersed in an ethanol-water mixed solution with a volume fraction of 15%, and sonicated for 30 minutes. A dispersion of 2% (w / w) zinc 8-hydroxyquinoline salt was prepared, which was used as a loading solution. Silane coupling agent-modified mesoporous silica was dispersed in the loading solution at a mass ratio of 1:0.2 to zinc 8-hydroxyquinoline salt. The mixture was stirred at room temperature for 24 hours for impregnation loading. After impregnation loading, the mixture was filtered, washed, and vacuum dried to obtain silane coupling agent-modified mesoporous silica loaded with a broad-spectrum antibacterial agent.

[0044] Based on the above, the specific implementation method of this application is as follows:

[0045] Example 1

[0046] Based on the above, a preferred embodiment of the present invention provides an antibacterial polycarboxylate superplasticizer, such as... Figure 1 As shown, it is prepared by the following method:

[0047] S1. Preparation of polycarboxylate superplasticizer mother liquor: Silane coupling agent modified mesoporous silica loaded with broad-spectrum antibacterial agent is added to a slow-release polycarboxylate polymer containing phosphate ester, and ultrasonically dispersed for 40 min to obtain polycarboxylate superplasticizer mother liquor; the mass ratio of silane coupling agent modified mesoporous silica loaded with broad-spectrum antibacterial agent to slow-release polycarboxylate polymer containing phosphate ester is 1:16.

[0048] S2. Preparation of antibacterial composition: A polycarboxylic acid polymer containing disulfide bonds was dissolved in deionized water to prepare a 15% (w / w) solution. Surface-epoxy-modified disulfide bond-modified mesoporous silica loaded with sulfate-reducing bacteria inhibitors was added. The mass ratio of the polycarboxylic acid polymer containing disulfide bonds to the surface-epoxy-modified disulfide bond-modified mesoporous silica loaded with sulfate-reducing bacteria inhibitors was 20:1. The mixture was stirred and reacted for 12 hours at pH 8.5 and a temperature of 40°C to obtain the antibacterial composition.

[0049] S3. Compounding: The polycarboxylate superplasticizer mother liquor and the antibacterial composition are compounded at a mass ratio of 14:3.3 and stirred evenly to obtain the antibacterial polycarboxylate superplasticizer.

[0050] Example 2

[0051] This embodiment differs from Embodiment 1 in that the polycarboxylate superplasticizer mother liquor and the antibacterial composition are compounded at a mass ratio of 14:3.0 and stirred evenly to obtain the antibacterial polycarboxylate superplasticizer.

[0052] Example 3

[0053] Based on Example 1, this embodiment differs from Example 1 in that the polycarboxylate superplasticizer mother liquor and the antibacterial composition are compounded at a mass ratio of 14:3.6 and stirred evenly to obtain the antibacterial polycarboxylate superplasticizer.

[0054] Comparative Example 1

[0055] The polycarboxylate superplasticizer provided in this comparative example comprises only a slow-release polycarboxylate polymer containing phosphate esters, which is an existing self-developed product of the applicant. The preparation method is as follows: 100g HPEG-2400 (methyl allyl alcohol polyoxyethylene ether, Mn=2400) was first reacted with succinic anhydride to introduce -COOH, and then esterified with phosphate-containing polyethylene glycol to obtain a functionalized polyether macromonomer (containing -COO-CH2-COO- linker groups). The functionalized polyether macromonomer, 25g acrylic acid, 3.5g vinylphosphonic acid, and 0.8g mercaptoacetic acid were then dissolved in 150g deionized water. N2 was passed through the solution for 30 minutes, and the temperature was raised to 60℃. An ammonium persulfate solution was added dropwise (dropping time was 2 hours). The ammonium persulfate solution was obtained by dissolving 1.2g of ammonium persulfate in 20g of deionized water. After the addition was completed, the temperature was maintained for 2 hours. Finally, the solution was cooled, and the pH was adjusted to 6.5 with NaOH to obtain a pale yellow liquid with a solid content of 40%. The pale yellow liquid is a slow-release polycarboxylic acid polymer containing phosphate esters. This product is a phosphate ester-type polycarboxylic acid water-reducing agent with slow-release function that the applicant has independently developed.

[0056] Comparative Example 2

[0057] Based on Example 1, the difference from Example 1 is that the antibacterial polycarboxylate superplasticizer provided in this comparison does not include the antibacterial composition, but all other aspects are the same.

[0058] Comparative Example 3

[0059] Based on Example 1, the difference from Example 1 is that the antibacterial polycarboxylate superplasticizer provided in this comparison does not include polycarboxylate polymers containing disulfide bonds in the antibacterial composition. The same amount of surface-epoxy-modified disulfide bond-modified mesoporous silica loaded with sulfate-reducing bacteria antibacterial agents as in Example 1 is directly added to the polycarboxylate superplasticizer mother liquor; all other aspects are the same.

[0060] Comparative Example 4

[0061] Based on Example 1, the difference from Example 1 is that the antibacterial polycarboxylate superplasticizer provided in this comparative example has a surface-epoxy-modified mesoporous silica in the antibacterial composition loaded with sulfate-reducing bacteria inhibitors, without disulfide bond modification, while the rest are the same; the surface-epoxy-modified mesoporous silica in this comparative example is prepared by the following method: 11.6g of... Triblock surfactant P123 was dissolved in 360 mL of deionized water and stirred until homogeneous. Then, tetraethyl orthosilicate, aluminum isopropoxide, and hydrochloric acid were added in a molar ratio of 0.017:1:0.04:6, and the reaction was continued for 24 hours. After the reaction was complete, the reaction solution was transferred to a hydrothermal reactor with a polytetrafluoroethylene liner and crystallized at 100 °C for 55 hours. After crystallization, the solution was filtered, washed with deionized water until neutral, and dried at 70 °C for 24 hours to obtain mesoporous silica powder. The mesoporous silica powder was then transferred to a Soxhlet extractor, acidified ethanol was added, and the mixture was refluxed at 85 °C for 48 hours. After filtration, the solution was washed with deionized water until neutral and dried under vacuum at 70 °C to obtain mesoporous silica.

[0062] 5g of mesoporous silica was dispersed in 100mL of anhydrous ethanol, and 2.5g of 3-glycidyl etheroxypropyltrimethoxysilane was added. The mixture was refluxed at 70℃ for 6 hours, filtered, washed with anhydrous ethanol, and dried under vacuum to obtain surface epoxy-modified mesoporous silica.

[0063] Comparative Example 5

[0064] Based on Example 1, the difference from Example 1 is that the antibacterial polycarboxylate superplasticizer provided in this comparative example does not have epoxy modification on the surface of the disulfide-modified mesoporous silica loaded with sulfate-reducing bacteria in the antibacterial composition; all other aspects are the same. The disulfide-modified mesoporous silica of this comparative example without epoxy modification was prepared by the following method: 11.6 g of triblock surfactant P123 was dissolved in 360 mL of deionized water at 35-40 °C. After stirring evenly, the mixture was prepared according to the following molar ratio: triblock surfactant P123, tetraethyl orthosilicate, bis-[3-(triethoxysilyl)propyl]-disulfide, aluminum isopropoxide, and hydrochloric acid were added in a ratio of 0.017:1:0.2:0.04:6. Stirring continued. The reaction mixture was stirred for 24 hours. After the reaction was completed, the reaction solution was transferred to a hydrothermal reactor with a polytetrafluoroethylene liner and crystallized at 100°C for 55 hours. After crystallization, the mixture was filtered, washed with deionized water until neutral, and dried at 70°C for 24 hours to obtain mesoporous silica powder. The mesoporous silica powder was transferred to a Soxhlet extractor, acidified ethanol was added, and the mixture was refluxed at 85°C for 48 hours. The mixture was filtered, washed with deionized water until neutral, and dried under vacuum at 70°C to obtain disulfide bond modified mesoporous silica.

[0065] Experimental Example 1

[0066] The initial slump and 2-hour slump retention rate of concrete prepared with polycarboxylate superplasticizers in Examples 1-3 and Comparative Example 1 were tested. The results are shown in Table 1. Three samples were used in each group, and the average value was taken.

[0067] Concrete mix composition: Cement: P·O42.5, 320 kg / m³; Water-cement ratio: 0.38; Sand ratio: 40%; Polycarboxylate superplasticizer dosage: 0.25% of the cementitious material mass; Mixing: Dry mix for 30 seconds, add water and polycarboxylate superplasticizer, wet mix for 60 seconds to obtain the tested concrete mix.

[0068] Slump Measurement Method: Slump is measured according to GB / T50080-2016, using a standard slump cone (inner diameter 100mm, height 300mm); the concrete is loaded in three layers, with each layer tamped 25 times; after lifting the cone, the slump height (mm) is measured; the initial slump (T=0min) is recorded; the concrete mixture is poured into a sealed container, covered with a film to prevent moisture evaporation; it is allowed to stand at room temperature (20℃±2℃) for 2 hours; the slump is measured again (slump at time t); slump retention rate (%) = (slump at time t / initial slump) × 100%.

[0069] Table 1 Slump test results

[0070] Example 1 220 94% Example 2 215 93% Example 3 220 93% Comparative Example 1 220 92%

[0071] The water-reducing agents prepared in Examples 1-3 of this application have comparable slump retention properties to the water-reducing agent in Comparative Example 1, indicating that the antibacterial composition and silane coupling agent modified mesoporous silica of this application do not have a negative impact on the slump retention properties of the water-reducing agent of this application.

[0072] Experimental Example 2

[0073] Concrete specimens: The water-reducing agents prepared in Examples 1-3 and Comparative Examples 1-5 were added as admixtures without any other admixtures. Concrete specimens (100mm×100mm×100mm) were formed according to the concrete formula of Test Example 1 and cured for 28 days according to standard before undergoing SRB corrosion testing. The results are shown in Table 2. The test groups of concrete specimens using the water-reducing agents prepared in Examples 1-3 as admixtures were designated as test group S1, test group S2, and test group S3, respectively. The test groups of concrete specimens using the water-reducing agents prepared in Comparative Examples 1-5 as admixtures were designated as test group D1, test group D2, test group D3, test group D4, and test group D5, respectively.

[0074] The seawater simulation environment for the SRB corrosion test: Weigh 5.2g of Postgate medium (provided by Haibo Biotechnology, catalog number HB8830) and 1.1g of sodium D-lactic acid (liquid substance), dissolve them in 1000ml of distilled water by heating, dispense into containers, and autoclave at 121℃ for 15min to obtain Postgate concentrate for later use; separately take Mocledon artificial seawater (salinity: 33.4%); under aseptic conditions, mix 100mL of sterilized Postgate concentrate with 900mL of artificial seawater to obtain a mixture; dispense the mixture into culture containers and autoclave at 121℃ for 15min; after cooling, purge with N2 to remove dissolved oxygen, and inoculate with SRB bacterial solution to an initial concentration of approximately 10. 6 CFU / mL was used to obtain a simulated seawater anaerobic culture system containing SRB; concrete specimens were placed in the simulated seawater anaerobic culture system containing SRB (initial SRB concentration approximately 10 CFU / mL). 6 (CFU / mL), and cultured at 35℃ for 90 days, with the simulated seawater anaerobic culture system containing SRB replaced every 2 weeks;

[0075] Control group 1 was set up as follows: An appropriate amount of SRB antibacterial agent (aminocyclodextrin-embedded 1,8-dichloroanthraquinone, without water-reducing agent loading) from Example 1 was directly added to the concrete mixture. The water-reducing agent prepared in Comparative Example 2 was used as an admixture. The concrete specimens prepared in the same way as in Experiment 1 were subjected to SRB corrosion test after 28 days of standard curing. This was used as control group 1.

[0076] Control group 2 was set up: an appropriate amount of SRB antibacterial agent (aminocyclodextrin-embedded 1,8-dichloroanthraquinone, without water-reducing agent loading) from Example 1 was directly added to the concrete mixture. The water-reducing agent prepared in Comparative Example 1 was used as an admixture. The concrete specimens prepared in the same way as in Experiment 1 were subjected to SRB corrosion test after 28 days of standard curing. This was used as control group 2.

[0077] Test items:

[0078] 1. Detection of SRB viable bacteria count on the surface of concrete after 90 days of SRB corrosion: Refer to standards HY / T 177-2014 and ASTM D4412; take samples from four sides of each concrete specimen, avoiding the top and bottom surfaces; demarcate a 50mm × 50mm sampling area in the center of each side for sampling and testing; use a sterile sampling drill bit to grind powder to a depth of 5mm from the surface of the demarcated area on each side, and collect the powder from each side independently; weigh 1g of sample from each side and place it in 9mL of sterile PBS (pH 7.2, containing 0.5mM Na2S·9H2O) pre-purified with N2, homogenize for 2min, and obtain the supernatant as 10. -1 Stock solution; serially diluted 10-fold to 10 -5 Based on the range of SRB bacterial count determined in the preliminary experiment, 10 -3 10 -4 10 -5 MPN counting was performed at three consecutive dilutions. Five test tubes (1 mL each) containing anaerobic Postgate C liquid medium were inoculated at each dilution. Lead acetate test paper was suspended under the cotton plug and the tubes were strictly anaerobic at 35±1℃ for 28 days. A positive result was defined as the appearance of black FeS precipitate at the bottom of the test tube and the blackening of the lead acetate test paper. The most probable number of SRBs was calculated according to the MPN table, and the result was expressed as MPN / g (surface wet mortar). The average value of the four sides was taken as the surface SRB viable count of the specimen. Three parallel specimens were tested in each group, and the result was expressed as the arithmetic mean of the average values ​​of the three specimens.

[0079] 2. Determination of the mass loss rate of concrete specimens after 90-day corrosion test: The constant weight drying method was used. The mass loss rate was calculated by comparing the dried mass of the concrete specimens before and after corrosion. Drying before corrosion: The concrete specimens were dried in an oven at 105±5℃ to constant weight (the difference between two weighings ≤0.1%), cooled to room temperature in a desiccator, and weighed, recorded as m0. After 90 days, the specimens were removed, and the corroded samples were dried in an oven at 105±5℃ to constant weight. After drying and cooling, they were weighed and recorded as m1. Mass loss rate (%) = (m0−m1) / m0×100%; Three parallel samples were used in each group, and the average value was taken.

[0080] 3. Surface pH of corroded concrete specimens: Samples were taken from four sides of each concrete specimen, avoiding the top and bottom surfaces. A 50mm × 50mm sampling area was demarcated in the center of each side for sampling and testing. Using a sterile sampling drill bit, powder was ground from the surface of the demarcated area on each side to a depth of 5mm. The powder samples from each side were collected independently. The powder samples from each side were added to deionized water at a solid-liquid ratio of 1g:2mL, shaken, and allowed to stand for 24 hours. The pH value of the extract was measured using a pH meter. The average value of the four sides was taken as the pH value of the specimen. Three parallel specimens were tested in each group, and the results were expressed as the arithmetic mean of the average values ​​of the three specimens.

[0081] Table 2 SRB corrosion test results

[0082] Example 1 S1 test group <![CDATA[2.8×10 2 ]]> 0.72% 10.6 Example 2 S2 test group <![CDATA[4.1×10 2 ]]> 0.85% 10.4 Example 3 S3 test group <![CDATA[3.5×10 2 ]]> 0.78% 10.5 Comparative Example 1 D1 test group <![CDATA[6.3×10 5 ]]> 4.28% 8.7 Comparative Example 2 D2 test group <![CDATA[5.1×10 5 ]]> 3.74% 8.9 Comparative Example 3 D3 test group <![CDATA[1.0×10 4 ]]> 1.82% 9.5 Comparative Example 4 D4 test group <![CDATA[3.8×10 4 ]]> 3.01% 9.0 Comparative Example 5 D5 test group <![CDATA[8.6×10 3 ]]> 1.56% 9.8 Comparative Example 2 Control group 1 <![CDATA[1.2×10 4 ]]> 2.28% 9.3 Comparative Example 1 Control group 2 <![CDATA[1.8×10 4 ]]> 2.67% 9.2

[0083] As shown in Table 2, this application exhibits good antibacterial activity against SRB. Combined with Table 1, while ensuring the performance of the water-reducing agent, it can use the water-reducing agent as a carrier to load the SRB antibacterial agent, demonstrating better antibacterial activity compared to existing directly applied SRB antibacterial agents. In Experimental Example 2, a comparison is made between the SEM images of the corrosion surfaces of the specimens in test group D1 and test group S1. Figure 2 As shown; the SEM image of the corroded surface of the specimen in test group D1 of this experiment is shown below. Figure 2 As shown in (a); SEM images of the corroded surface of the specimens in test group S1 are shown below. Figure 2 As shown in (b), in comparison Figure 2 (a) Figure 2 (b) The surface of the sample in test group S1 is as follows: Figure 2 As shown in (b), the corrosion level is lower. The antibacterial water-reducing agent prepared in Example 1 of this application, when incorporated into concrete, has the effect of resisting SRB biocorrosion.

[0084] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, and improvements made by those skilled in the art within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. An antibacterial polycarboxylate superplasticizer, characterized in that: Includes polycarboxylate superplasticizer mother liquor and antibacterial composition; The polycarboxylate superplasticizer mother liquor includes a slow-release polycarboxylate polymer containing phosphate esters and silane coupling agent modified mesoporous silica, wherein a broad-spectrum antibacterial agent is loaded on the silane coupling agent modified mesoporous silica. The antibacterial composition includes a polycarboxylic acid polymer containing disulfide bonds and surface-epoxy-modified disulfide bond-modified mesoporous silica, on which sulfate-reducing antibacterial agents are loaded. Surface-modified disulfide-bonded mesoporous silica was prepared by the following method: Triblock surfactant P123 was dissolved in deionized water at 35-40℃, followed by the addition of tetraethyl orthosilicate, bis-[3-(triethoxysilyl)propyl]-disulfide, aluminum isopropoxide, and hydrochloric acid. The mixture was stirred for 24-28 hours. After the reaction, the reaction solution was transferred to a hydrothermal reactor with a polytetrafluoroethylene liner and crystallized at 90-110℃ for 55-56 hours. After crystallization, the solution was filtered, washed with deionized water until neutral, and then crystallized at 60℃. The raw mesoporous silica powder was obtained by drying at 80℃ for 22-24 hours. The raw mesoporous silica powder was transferred to a Soxhlet extractor, acidified ethanol was added, and the mixture was refluxed at 80-90℃ for 40-48 hours. The mixture was filtered, washed with deionized water until neutral, and dried under vacuum at 60-80℃ to obtain disulfide-modified mesoporous silica. The molar ratio of triblock surfactant P123, tetraethyl orthosilicate, bis-[3-(triethoxysilyl)propyl]-disulfide, aluminum isopropoxide, and hydrochloric acid was 0.017:1:0.2:0.04:

6. Disulfide-modified mesoporous silica was dispersed in anhydrous ethanol, and 3-glycidyl etheroxypropyltrimethoxysilane was added. The mixture was refluxed at 60–80 °C for 4–8 hours, filtered, washed with anhydrous ethanol, and vacuum dried to obtain epoxy-modified disulfide-modified mesoporous silica. The mass ratio of disulfide-modified mesoporous silica to 3-glycidyl etheroxypropyltrimethoxysilane was 2:

1. The broad-spectrum antibacterial agent is 8-hydroxyquinoline zinc salt; the sulfate-reducing antibacterial agent is 1,8-dichloroanthraquinone encapsulated in aminocyclodextrin. Surface-epoxy-modified disulfide-bonded mesoporous silica was loaded with sulfate-reducing antibacterial agents using the following method: 1,8-dichloroanthraquinone, encapsulated with aminocyclodextrin, was dissolved in N,N-dimethylformamide to prepare a 10% (w / w) loading solution; the surface-epoxy-modified disulfide-bonded mesoporous silica was dispersed in the loading solution at a mass ratio of 1:0.3 to 1:0.3; impregnation loading was carried out by stirring at room temperature for 24 hours, with the pH controlled at 7.0–8.0 during the impregnation loading process; after impregnation loading, the silica was filtered, washed 2–3 times with anhydrous ethanol, and vacuum dried at 40–50°C to constant weight. The silica was then stored in a sealed container away from light to obtain surface-epoxy-modified disulfide-bonded mesoporous silica loaded with sulfate-reducing antibacterial agents.

2. The antibacterial polycarboxylate superplasticizer according to claim 1, characterized in that: The polycarboxylic acid polymer containing disulfide bonds is obtained by copolymerizing isopentenyl polyoxyethylene ether macromonomer, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid and a polymerizable intermediate containing disulfide bonds under the action of an initiator and a chain transfer agent.

3. The antibacterial polycarboxylate superplasticizer according to claim 1, characterized in that: The slow-release polycarboxylic acid polymer containing phosphate esters is obtained by copolymerizing vinylphosphonic acid, acrylic acid, and functionalized polyether macromonomers under the action of an initiator and a chain transfer agent; wherein, the functionalized polyether macromonomer is a polyether macromonomer obtained by pre-reacting HPEG-2400 with succinic anhydride and then esterifying it with phosphate-containing polyethylene glycol.

4. The antibacterial polycarboxylate superplasticizer according to claim 1, characterized in that: The aminocyclodextrin-encapsulated 1,8-dichloroanthraquinone was prepared by the following method: Mono-6-amino-β-cyclodextrin was dissolved in deionized water to prepare a 5% (w / w) aminocyclodextrin aqueous solution; 1,8-dichloroanthraquinone was dissolved in dimethyl sulfoxide to prepare a 20 mg / mL anthraquinone organic solution; under light-protected stirring at 20-30°C, the anthraquinone organic solution was added dropwise to the aminocyclodextrin aqueous solution, with a molar ratio of mono-6-amino-β-cyclodextrin to 1,8-dichloroanthraquinone of 1:0.6; after the addition was complete, stirring was continued for 6 hours in the dark, followed by vacuum distillation. The remaining liquid was pre-frozen at -40 to -20°C for 3 hours, then freeze-dried for 30 hours, and stored in a sealed container in the dark to obtain aminocyclodextrin-encapsulated 1,8-dichloroanthraquinone.

5. The antibacterial polycarboxylate superplasticizer according to claim 1, characterized in that: Silane coupling agent modified mesoporous silica loaded with broad-spectrum antibacterial agent was prepared by the following method: SBA-15 mesoporous silica was dispersed in anhydrous ethanol, and silane coupling agent KH-550 was added. The mass ratio of KH-550 to SBA-15 mesoporous silica was 0.15:

1. The mixture was refluxed at 60-80℃ for 6 hours, filtered, washed with anhydrous ethanol, and vacuum dried to obtain silane coupling agent modified mesoporous silica. 8-Hydroxyquinoline zinc salt was dispersed in an ethanol-water mixture with a volume fraction of 15% ethanol and sonicated for 20-40 min to prepare a dispersion with a mass concentration of 2% 8-hydroxyquinoline zinc salt, which was used as the loading solution. Silane coupling agent modified mesoporous silica was dispersed in the loading solution at a mass ratio of 1:0.2 to 1. The mixture was stirred at room temperature for 24 hours for impregnation loading. After impregnation loading, the mixture was filtered, washed, and vacuum dried to obtain silane coupling agent modified mesoporous silica loaded with a broad-spectrum antibacterial agent.

6. A method for preparing an antibacterial polycarboxylate superplasticizer according to any one of claims 1-5, characterized in that: Includes the following steps: S1. Preparation of polycarboxylate superplasticizer mother liquor: Silane coupling agent modified mesoporous silica loaded with broad-spectrum antibacterial agent is added to a slow-release polycarboxylate polymer containing phosphate ester, and ultrasonically dispersed for 20-40 min to obtain polycarboxylate superplasticizer mother liquor; the mass ratio of silane coupling agent modified mesoporous silica loaded with broad-spectrum antibacterial agent to slow-release polycarboxylate polymer containing phosphate ester is 1:

16. S2. Preparation of antibacterial composition: A polycarboxylic acid polymer containing disulfide bonds is dissolved in deionized water to prepare a 15% (w / w) solution. Surface-epoxy-modified disulfide bond-modified mesoporous silica loaded with sulfate-reducing bacteria inhibitors is added. The mass ratio of the polycarboxylic acid polymer containing disulfide bonds to the surface-epoxy-modified disulfide bond-modified mesoporous silica loaded with sulfate-reducing bacteria inhibitors is 20:

1. The mixture is stirred and reacted for 12 hours at pH 8.0–9.0 and temperature 35–45°C to obtain the antibacterial composition. S3. Compounding: The polycarboxylate superplasticizer mother liquor and the antibacterial composition are compounded at a mass ratio of 14:(3.0~3.6) and stirred evenly to obtain the antibacterial polycarboxylate superplasticizer.

Citation Information

Patent Citations

  • Antibacterial polycarboxylate superplasticizer and preparation method thereof

    CN112794958A

  • Phosphate type polycarboxylate superplasticizer with slow release function, preparation method of phosphate type polycarboxylate superplasticizer, concrete admixture composition and application of concrete admixture composition

    CN121537574A